2007
DOI: 10.1111/j.1467-9280.2007.01944.x
|View full text |Cite
|
Sign up to set email alerts
|

Action Anticipation Through Attribution of False Belief by 2-Year-Olds

Abstract: Two-year-olds engage in many behaviors that ostensibly require the attribution of mental states to others. Despite this, the overwhelming consensus has been that they are unable to attribute false-beliefs at this age. In the current study, we have used an eye-tracker to record infant's looking behaviour while they watched actions on a computer monitor. Our data demonstrate that 25-month-old infants show correct anticipation of an actor's actions that could only be predicted if they had attributed a false belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
936
14
11

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 821 publications
(1,008 citation statements)
references
References 41 publications
47
936
14
11
Order By: Relevance
“…This growing body of evidence casts doubt on the notion that infants' successful performance in falsebelief tasks is the result of primitive abilities that apply to only a limited range of situations and behaviors. Such findings instead support recent mentalistic accounts, which propose that infants make sense of agents' behavior by reasoning about their motivational, epistemic, and counterfactual states (e.g., Baillargeon, Scott, & Bian, 2016;Baillargeon et al, 2010;Barrett et al, 2013;Buttelmann et al, 2009;Carruthers, 2013;Kovács et al, 2010;Luo, 2011;Scott et al, 2010;Southgate et al, 2007;Surian et al, 2007).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This growing body of evidence casts doubt on the notion that infants' successful performance in falsebelief tasks is the result of primitive abilities that apply to only a limited range of situations and behaviors. Such findings instead support recent mentalistic accounts, which propose that infants make sense of agents' behavior by reasoning about their motivational, epistemic, and counterfactual states (e.g., Baillargeon, Scott, & Bian, 2016;Baillargeon et al, 2010;Barrett et al, 2013;Buttelmann et al, 2009;Carruthers, 2013;Kovács et al, 2010;Luo, 2011;Scott et al, 2010;Southgate et al, 2007;Surian et al, 2007).…”
Section: Discussionsupporting
confidence: 65%
“…The results of such tasks suggested that the ability to attribute false beliefs to others did not emerge until at least 4 years of age (for reviews, see Devine & Hughes, 2014;Wellman, Cross, & Watson, 2001). Recently, however, researchers have developed a number of alternative paradigms for assessing false-belief understanding in much younger children (e.g., Buttelmann, Carpenter, & Tomasello, 2009;Kovács, Téglás, & Endress, 2010;Luo, 2011;Onishi & Baillargeon, 2005;Scott, Baillargeon, Song, & Leslie, 2010;Southgate, Senju, & Csibra, 2007). Positive results have now been obtained with infants aged 8 to 25 months using a variety of response measures (for reviews, see Baillargeon et al, 2015;Scott, Roby, & Smith, in press), leading many investigators to conclude that the capacity to attribute false belief to others emerges by at least the end of the first year of life (e.g., Baillargeon, Scott, & He, 2010;Barrett et al, 2013;Buttelmann et al, 2009;Carruthers, 2013;Kovács et al, 2010;Luo, 2011;Scott, in press;Southgate et al, 2007;Surian, Caldi, & Sperber, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is even evidence that children can pass versions of the false belief task before the age of three (Buttelmann et al 2009;Chandler et al, 1989;Kovács et al 2010;;Southgate et al 2007;Surian et al, 2007) with some evidence suggesting that children as young as 15-months can pass some versions of the false belief task (Onishi and Baillargeon, 2005). Again, to take just one example, in a study where children had to actively deceive a protagonist, Chandler, Fritz and Hala (1989) found that children as young as 2 ½ years of age were successful in misleading a target protagonist.…”
Section: Evidence From Theory Of Mind Tasksmentioning
confidence: 99%
“…Work on how children reason about other agents' goals [1][2][3][4][5][6][7][8], desires [9][10][11], beliefs [12][13][14][15][16][17][18], and pro-social behavior [19][20][21][22][23][24][25][26][27][28][29] has advanced our understanding of what in our commonsense psychology is at work in early infancy [30][31][32] and what develops [16][17][33][34][35]. Nonetheless, major theoretical questions remain unresolved.…”
Section: Commonsense Psychologymentioning
confidence: 99%